The effect of fatigue on first stance phase kinetics during acceleration sprint running in professional football players - Wdowski, M. M.; Clarke, N.; Eyre, L. J. L.; Morris, R.; Noon, M.; Eustace, J. S.; Hankey, J.; Raymond, M. L.; Richardson, L. D. (Science and Medicine in Football, 2021)
Nineteen professional football players (Age: 26±5 years; Height: 1.84±0.08 m; Mass: 83.4±8.9 kg) completed three x 30 m maximal acceleration sprints from a standing start before completing the Yo-Yo intermittent recovery test level 1. Three x 30 m maximal acceleration sprints were then repeated post-fatigue. Light gates recorded sprint times from 0-5 m, 0-10 m, 0-15 m and 0-30 m. Force platforms collected ground reaction force of the first stance phase of the sprint run. Differences between pre- and post-fatigue were observed in the sprint times over 0-15 m (P = 0.015; CI [0.007, 0.110]) and 0-30 m (P = 0.004; CI [0.056, 0.234]). Peak medial-lateral ground reaction force was lower (P = 0.045; CI [-0.146, -0.005]) post- than pre-fatigue. The ratio of force were significantly different between pre- and post-fatigue for the medial-lateral and anterior-posterior comparison (P = 0.017; CI [-0.063, -0.010]), and the medial-lateral and vertical comparison (P = 0.012; CI [-0.036, -0.007]). Football players altered their sprint mechanics to reduce medial-lateral loading and orient the force in an increased anteroposterior and vertical direction in order to maintain 0-10 m sprint performance. Practitioners should observe medial-lateral force contributions and improve sprint technical efficacy.